2017
DOI: 10.1016/j.spinee.2016.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Objective measurement of free-living physical activity (performance) in lumbar spinal stenosis: are physical activity guidelines being met?

Abstract: BACKGROUND Research suggests that people with lumbar spinal stenosis (LSS) would benefit from increased physical activity. Yet, to date, we do not have disease-specific activity guidelines for LSS, and the nature of free-living physical activity (performance) in LSS remains unknown. LSS care providers could endorse the 2008 United States Physical Activity Guidelines; however, we do not know if this is realistic. The goal of the present study was to determine the proportion of individuals with LSS meeting the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 55 publications
(50 reference statements)
1
20
0
Order By: Relevance
“…This suggests that a majority of the patients in our study do not reap the health benefits of being sufficiently physically active and are therefore at risk of developing additional disease and poor health [ 7 ]. Similar findings have been found by Mobbs et al, [ 16 ] and Norden et al, [ 21 ]. Mobbs et al studied a mixed group of patients with degenerative lumbar disorders and found that the mean value for the variable “steps per day” (5255 steps) was below the threshold for a physically active lifestyle [ 16 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This suggests that a majority of the patients in our study do not reap the health benefits of being sufficiently physically active and are therefore at risk of developing additional disease and poor health [ 7 ]. Similar findings have been found by Mobbs et al, [ 16 ] and Norden et al, [ 21 ]. Mobbs et al studied a mixed group of patients with degenerative lumbar disorders and found that the mean value for the variable “steps per day” (5255 steps) was below the threshold for a physically active lifestyle [ 16 ].…”
Section: Discussionsupporting
confidence: 92%
“…They also used an accelerometer but only presented the variable as “steps per day”. Norden et al showed that only 4% of their patients with spinal stenosis met the physical activity recommendations before decompression surgery [ 21 ]. Moreover, a recently published systematic review and meta-analysis by Koenders et al, [ 45 ], concluded that “research should provide more information regarding the clinical care pathway, psychosocial and physical conditions of the patients undergoing first time lumbar fusion surgery, and without this information, it remains impossible to improve lumbar fusion surgery management” .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a systematic review of the literature, accelerometer and physical activity analyses using wearable devices ranked among the top five most frequently applied methods for objective outcome measurement in spine care 4 . To date, the activity levels of about 340 patients with lumbar degenerative diseases of the spine have been reported in nine research articles, which included patients with low back pain (LBP), lumbar spinal stenosis (LSS) and lumbar disc herniation (LDH) [8][9][10][11][12][13][14][15][16] .…”
mentioning
confidence: 99%